Measurement of Sustainable Agriculture at Household Level: Results of Indonesian Agriculture Integrated Survey (AGRIS) Pilot - Kadir Kadir; Isnaeni Nur Khasanah; Eka Rudiana (Politeknik Statistika STIS, 2021)
This study aims to measure and analyzes the level of agricultural sustainability at the household level using the results of the Integrated Agricultural Survey (AGRIS) pilot conducted by Statistics Indonesia in 2020. Applying descriptive analysis on the computation results of eleven sub-indicators of the SDGs 2.4.1 indicator at the household level, we analyzed the proportion of agricultural households categorized as sustainable and unsustainable for each corresponding sub-indicator of sustainability. We also estimated the average land area managed by agricultural households for each category in each sub-indicators. We found that most agricultural households in West Java, East Java and West Nusa Tenggara are categorized as unsustainable in agricultural practices regarding land productivity. The proportion of households practising unsustainable agriculture are also quite large regarding fertilizer use and decent employment. We also found that less land productivity and poor management of fertilizer use are the phenomena of a relatively large scale farm.